Elucidating membrane surface properties for preventing fouling of bioreactor membranes by surfactin. Issue 21 (11th November 2014) - Behary, Nemeshwaree; Lecouturier, Didier; Perwuelz, Anne; Dhulster, Pascal; Escobar, Isabel C.; Van der Bruggen, Bart
ABSTRACT The large scale production of bacterial surfactin‐an anionic lipopeptide is restricted by its high cost of production. Surface sorption of surfactin causes membrane fouling, decreasing air permeation, or filtration efficiency of membranes used in bioreactors. The aim of this study was to elucidate surface properties leading to reduction or even the prevention of surfactin sorption on fibrous membranes. Surface modification of fibrous polyethylene terephthalate (PET) nonwoven membranes using cationic and/or anionic biopolymers, or an antiadhesive fluorinated polymer, with or without a prior air plasma treatment, resulted in membranes with varying surface properties. Membranes with superhydrophilic to superhydrophobic behavior with varying surface charges (positive, nul, and negative) were produced. Water contact angle (WCA), capillary uptake, as well as Zeta potential of each modified membrane, were quantified. Sorption tests using surfactin, were carried during 5, 24, and 48 h, at pH 7. The amphiphilic anionic lipopeptide sorbed on positively charged membranes as well as on negatively charged hydrophobic, hydrophilic, or superhydrophobic membranes. PET membrane functionalized with alternate deposition of chitosan and alginate presented surface properties (zeta potential of −20 mV and WCA = 80°), which was effective in rejecting 100% of the anionic surfactin both at an initial stage and at a late stage (after 48 h). Discussion is proposed to explain possible interactions between the anionic lipopeptide and the functionalized nonwovens. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41622.